A botanist's guide to flowers and fatality - Khavari, Kate (Khavari, Kate. Saffron Everleigh mystery, 2023)
"Saffron embarks on her first research study alongside the insufferably charming Dr. Michael Lee, traveling the countryside with him in response to reports of poisonings. But when Detective Inspector Green is given a case with a set of unusual clues, he asks for Saffron's assistance. The victims, all women, received bouquets filled with poisonous flowers. Digging deeper, Saffron discovers that the bouquets may be more than just unpleasant flowers--there may be a hidden message within them, revealed through the use of the old Victorian practice of floriography. A dire message, indeed, as each woman who received the flowers has turned up dead. Alongside Dr. Lee and her best friend, Elizabeth, Saffron trails a group of suspects through a dark jazz club, a lavish country estate, and a glittering theater, delving deeper into a part of society she thought she'd left behind forever"--